Analisis Laporan Keuangan Pada Fore Coffee (Jurnal Riset Manajemen dan Akuntansi, 2025)
This study analyzes Fore Coffee's financial condition in the period 2021 to 2022 with a focus on the company's liquidity, solvency, and profitability. The results of the analysis show that liquidity ratios such as the current ratio, quick ratio, and cash ratio are at a low level, indicating the company's limited ability to meet short-term obligations. In terms of solvency, Fore Coffee faces high financial risk because total debt exceeds assets and equity, so a better financial management strategy is needed to balance the capital structure. Nevertheless, profitability performance shows positive developments with an increase in Return on Assets (ROA), indicating an improvement in the utilization of assets to generate profits. However, Return on Equity (ROE) is still negative due to the equity value that has not strengthened. Overall, Fore Coffee has promising growth potential, but needs to make improvements in financial management so that operational stability and sustainability can be maintained in the future.